INHIBITION OF ENZYME ACTIVITY OF TYROSINASE WITH EDTA, CHITOSAN AND PAPAIN - Cjuno H., J. (2009)
With the objective of the browning controlling enzymatic in fruits, a sequence of experiments of enzymatic inhibition has been developed based on the system enzyme-sustrato-inhibitor (tyrosinase-pyrocatechol-inhibitor).The enzymatic activity of the tyrosinase has been substantially affected by the chelating inhibitors (EDTA), polymeric (chitosane) and enzymatic (papain). The inhibitory effectiveness of the papain has been attributed to its hydrolitic action on the active places 176G and 182E of the tyrosinase. An approach for the constant of Michaelis (Km at 25°C) has given the value of 2,0.